Genital disease in children. I. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
The female genital apparatus consists of ovary, uterine salpinx, vagina and vulva. The vulva (female pudendum) includes female external genital organs. The latter consist of labia maiora, namely two large, sagittally oriented cutaneous folds, which delimit a cleft named rima of the pudendum. The upper extremities of the labia maiora continue with a cutaneous protuberance (mons of the pudendum or Venus mons). Inside the labia maiora there are other two cutaneous fold, named labia minora, which join in front with clitoris. In the vestibulum of the vagina, which is a little fossa delimited by labia maiora and minora, open urethra and vagina. The clitoris and the bulbs of the vestibulum are the erectile organs of the vulva. The male genital apparatus consists of testicles, sperm ducts, penis, various formations related to testicle such as scrotum and involucra of testicle and, finally, some glands related to urethra such as prostate and bulb-urethral glands. The penis consists of a root, a body and an anterior extremity or glans of the penis. The latter is separated from the body of the penis by a circular groove or balanopreputial groove. On the top of the glans of the penis there is the external urethral meatus, a little cleft that is located in sagittal position. The glans presents at its basis a raised border or corona of the glans and on its lower aspect a median groove (median groove of the glans). The glans is more or less completely covered by a cutaneous fold, the foreskin, which is an extension of the skin covering the body of the penis, able to run along the longitudinal axis of the penis. The foreskin is fixed to the ventral aspect of the glans by a sagittal fold, the bridle of the foreskin. When the foreskin covers the glans, between its internal layer and the glans itself originates a cavity called balano-preputial sac.